What's Love Got to Do with It: Relationship Functioning and Mental and Physical Quality of Life Among Pregnant Adolescent Couples. Issue 3 (4th October 2013) - Kershaw, Trace; Murphy, Alexandrea; Divney, Anna; Magriples, Urania; Niccolai, Linda; Gordon, Derrick
Abstract: The study objective was to describe relationship adjustment and its association with mental and physical quality of life for young couples expecting a baby. 296 young pregnant couples recruited from urban obstetric clinics reported on relationship strengths (e.g., equity, romantic love, and attractiveness), relationship risks (e.g., attachment, intimate partner violence), external family support, relationship adjustment, and mental and physical quality of life. Using the Actor Partner Interdependence Model we assessed both actor and partner effects of relationship variables on relationship adjustment and quality of life. Sixty‐one percent of couples had at least one member with moderate or severe relationship distress. Lower attachment avoidance, lower attachment anxiety, higher relationship equity, lack of intimate partner violence, feelings of love, perceived partner attractiveness, and family support of the relationship related to better relationship adjustment. Associations were fairly consistent across gender. Better relationship adjustment related to more positive mental and physical quality of life for both young women and men. Our results highlight the potential importance of strong relationships on the well‐being of expecting parents. Our results suggest that secure attachments, equitable relationships, feelings of love, and a lack of violence may be particularly important in having strong relationships and improved mental and physical health during pregnancy.